2003
DOI: 10.1034/j.1399-3038.2003.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids in breast milk of allergic and non‐allergic mothers: The PIAMA birth cohort study

Abstract: Fatty acid composition was studied in breast milk of allergic and non-allergic mothers, focusing in particular on concentrations of the n-6 and n-3 long-chain polyunsaturates (LCP) in relation to maternal allergy. Milk samples were obtained from 168 mothers with asthma or inhalant allergies and 107 mothers without asthma and inhalant allergies, between 2 and 35 weeks after delivery. Mean values of fatty acid concentration (weight% of total fatty acids) were estimated for individual fatty acids, for groups of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…In a previous study, we compared breast milk FA concentrations in mothers with and without allergy. 21 We found no differences between the 2 groups except for a small but statistically significant difference in the mean ratio n-6LCP/18:2n-6 in their breast milk. In the current study, we assessed the relationship between the FA content of these mothers' breast milk and allergic symptoms in their children at the ages of 1 and 4 years.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In a previous study, we compared breast milk FA concentrations in mothers with and without allergy. 21 We found no differences between the 2 groups except for a small but statistically significant difference in the mean ratio n-6LCP/18:2n-6 in their breast milk. In the current study, we assessed the relationship between the FA content of these mothers' breast milk and allergic symptoms in their children at the ages of 1 and 4 years.…”
mentioning
confidence: 73%
“…FA composition of the breast milk was determined by gas liquid chromatography, as described by Foremanvan Drongelen et al 23 Details of breast milk collection and analysis have been reported elsewhere. 21 To assess evidence for the hypotheses described in the introduction, the following FA and ratios were selected as exposure variables (out of the total number of 34 individual FA measured): linoleic acid (LA; 18:2n-6), a-linolenic acid (ALA; 18:3n-3), AA (20:4n-6), eicosapentaenoic acid (EPA; 20:5n-3), docosahexaenoic acid (DHA; 22:6n-3), total n-6LCP, total n-3LCP, the ratio ALA/LA (18:3n-3/ 18:2n-6), the ratio EPA/AA (20:5n-3/20:4n-6), the ratio n-3LCP/ n-6LCP, and total trans FA.…”
Section: Exposure Assessmentmentioning
confidence: 97%
“…However, several epidemiological studies have shown that the fatty acid composition in milk and other nutrients affect the development of allergy and asthma. This effect has been attributed to the anti-inflammatory and immune-modulating effects of omega-3 (n-3) fatty acids [65][66][67][68][69]. It is interesting to note that ACSL3 is located in 2q36.1, a region that has been recently shown to be associated with asthma susceptibility [70,71].…”
Section: Policyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…In general, exclusive breastfeeding for a period of 4 to 6 month is recommended as a method of primary allergy prevention (Arshad 2004), although published data on the subject is somewhat confl icting. While most studies confi rm preventive effects (Kull et al 2004, Kull et al 2005, Laubereau et al 2004, van Odijk et al 2003, Wijga et al 2003, several studies have found an increased risk for the development of atopic eczema or asthma for breastfed babies (Bergmann et al 2002, Purvis et al 2005, Sears et al 2002, Siltanen et al 2003. In this context, the composition of breast milk regarding allergen content, immune mediators and nutrients is important, though most studies lack this information.…”
Section: Breastfeedingmentioning
confidence: 99%